Knowledge based assessment of trained certified farm advisors (CFA) on organic farming - BHANU, CHANDRA; RAVISANKAR, N; GHASAL, P C; CHOUDHARY, JAIRAM; SINGH, RAGHUVEER; RAGHVENDRA, K J; MEENA, A L; MEENA, L K; DUTTA, D; MISHRA, R P; BALASUBRAMANI, N; SADALAXMI, A; et al. (The Indian Journal of Agricultural Sciences, 2022)
An inter-organizational certificate course i.e. Certified Farm Advisor (CFA) in Organic Farming was jointly organized by National Institute of Agricultural Extension Management (MANAGE), Hyderabad and ICAR-Indian Institute of Farming Systems Research, Modipuram, Meerut during 2019. The objective of this certificate course was to create a cadre of â€œCertified Farm Advisorsâ€ in appropriate technologies of organic farming and enable them to deliver effective â€œTechnical Advisory Servicesâ€ and thereby solving the field level problems faced by the organic farmers/entrepreneurs/startups or other related stakeholders. A 15 days CFA module II was organized at ICAR- Indian Institute of Farming Systems Research, Modipuram, Meerut in two batches with 50 trainees from 15 different states and union territories. In the present study, the learning, knowledge and skill levels of the participants were analyzed. Multiple regression analysis showed that, gender, service experience and serving region significantly affected the learning ability of trainees. There was significant improvement in the knowledge and skill of trainees in various aspects of organic farming, viz. organic standards, certification and marketing network (study area A); technology package (study area B) and general knowledge (study area C). Based on the training effectiveness scores (TES), maximum improvement was observed with general knowledge of organic farming with 103.73% improvement. However, study area A and B exhibited 45.41% and 34.88% improvement, respectively. Further, the success of this inter-organizational training programme could serve as a model for streamlining HRD programmes on organic farming in the country.